1992
DOI: 10.1056/nejm199209243271302
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis C Virus RNA in Organ Donors Positive for Hepatitis C Antibody and in the Recipients of Their Organs

Abstract: Nearly all the recipients of organs from anti-HCV-positive donors become infected with HCV. The current tests for anti-HCV antibodies underestimate the incidence of transmission and the prevalence of HCV infection among immunosuppressed organ recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
1
3

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(81 citation statements)
references
References 25 publications
4
73
1
3
Order By: Relevance
“…We detected HCV RNA in the saliva of 83% of our HCVpositive sicca syndrome patients and in none of our sicca syndrome patients without HCV RNA in their serum. Our results might be related to blood contamination of the saliva samples, as has been shown for organs removed from infected donors (36). However, we believe that the presence of HCV in the salivary glands might result in the stimulation of B lymphocytes and triggering of the immune process.…”
Section: Discussionmentioning
confidence: 56%
“…We detected HCV RNA in the saliva of 83% of our HCVpositive sicca syndrome patients and in none of our sicca syndrome patients without HCV RNA in their serum. Our results might be related to blood contamination of the saliva samples, as has been shown for organs removed from infected donors (36). However, we believe that the presence of HCV in the salivary glands might result in the stimulation of B lymphocytes and triggering of the immune process.…”
Section: Discussionmentioning
confidence: 56%
“…[3][4][5][6][7][8][9][10] Potential exposures that were evaluated in case control studies of acute disease and found not be associated with acquiring hepatitis C included medical, surgical, or dental procedures, tattooing, acupuncture, ear piercing, incarceration, military service, or foreign travel. 7,8 While recent histories of health carerelated procedures were commonly reported by both cases and controls (about 30%), a recent history of potential exposures such as tattooing was reported by less than 1% of both cases and controls.…”
Section: Risk Factors Associated With Acquiring Hcv Infectionmentioning
confidence: 99%
“…Transmission of HCV from an HCVpositive organ donor to an HCV-negative recipient in solid organ transplantation has been well documented, [3][4][5] and the subsequent development of chronic hepatitis leading to cirrhosis and end-stage liver disease has been described. [4][5][6][7] Although the outcome of renal and liver transplant recipients infected with HCV has been extensively investigated, 6,8 the transmission of HCV and the outcome of de novo HCV infection in heart transplant recipients remains to be determined.…”
mentioning
confidence: 99%